Reliability Analysis of Bucket-Wheel Excavator Parts – Application of Critical Position Selection Algorithm - Branković, Dejan; Milovanović, Zdravko; Janièić-Milovanović, Valentina (Journal of Graphic Era University, 2024)
Mining machines represent complex technical systems exposed to very difficult and demanding working conditions. The requirement of a high degree of effectiveness of technical systems in surface mines conditions a special organization of maintenance. The maintenance imperative is to ensure high reliability of parts of technical systems. For the maintenance of complex systems, made up of a large number of components, the parts whose failures cause the greatest negative consequences for the complete production system are particularly important. Analysis of the criticality of parts of technical systems directs maintenance activities to the prevention of failure states on key elements and ensuring the highest possible degree of their reliability. The paper presents the methodology of defining the critical position of the technical system Bucket-Wheel Excavator – belt conveyor – dumper on the open pit using the critical position selection algorithm. The basic criterion for choosing a critical position is a comparison of the frequency of failure and the reliability of individual components of technical systems. The results of the analysis confirm the connection of the statistical data analysis of the number of failure states of the working positions of the technical system with empirically determined reliability functions according to the methodology of non-parametric determination of reliability. The presented algorithm represents a methodology for recognizing the critical elements of technical systems whose operation has the greatest impact on the stability of the functioning of the complete technical system. Optimizing critical positions reduces total system downtime, increases productivity and improves overall business results.